Coastal zone planning and management proceedings of the conference Coastal management '92 integrating coastal zone planning and management in the next century, organized by the Institution of Civil Engineers and held in Blackpool on 11-13 May 1992 - Barrett, M. G. (Thomas Telford, 1992)
Given the ever increasing awareness of coastal planning and management on an integrated basis, this volume compounds the general change in perspective.